Prevention of Acute Kidney Injury Related (AKI) related by vancomycin; A Randomized Clinical Trial - Mahboubeh Neamatshahi; Aghil Keykhosravi; Anoush Azarfar; Yalda Ravanshad; Yosra Mohammadi; Anahita Ataran; Omid Rashidi; Elham Navipour; Homan Tehrani (Patient Safety and Quality Improvement Journal)
Introduction:Acute kidney injury (AKI) is one of the potential side effects of vancomycin in children with systemic infections. We aimed to evaluate the effect of selenium on the prevention of Vancomycin-associated AKI (VA-AKI)Materials and Methods: This study is a parallel randomized controlled trial in Heshmatieh Hospital, Sabzevar, Iran. According to the simple random sampling method, thirty patients between 1 month and 18 years old with systemic infections were randomly assigned to two groups. The intervention and control groups were treated with vancomycin plus selenium and vancomycin alone, respectively. Urine and blood samples were obtained from patients at the beginning and seven days after the treatment to evaluate AKI among patients.Results: We found no significant difference between baseline BUN, creatinine, and microalbumin in the two groups (P>0.05). There was a significant difference between the two groups post-treatment urine microalbumin (P= 0.045). The frequency of AKI in the intervention group [5(33.3%)] was lower than the control group [11(73.3%)] (P = 0.02). There were few changes between the mean difference baseline and post-treatment Cr (0.1mg/dl) and BUN (2.9mg/dl). Drug efficacy was 66%, and the number needed to treat (NNT) was equal to 2.Conclusion:In the present study, we concluded that selenium could prevent vancomycin-induced AKI. Future investigations on the higher numbers of patients are needed.